1981
DOI: 10.1136/ard.40.6.541
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and echocardiographic study of patients with the hypermobility syndrome.

Abstract: SUMMARY Three age-and symptom-matched groups of patients with a hypermobility score of 5-9, 3-4, and 0-2 (controls), respectively, were examined for clinical and echocardiographic evidence of mitral valve prolapse and other stigmata of a collagen disorder. Mitral valve prolapse, a reduced upper segment/lower segment mitral ratio, reduced skin thickness, spinal anomalies, and a history of fracture were found to be significantly commoner among the hypermobile patients than the controls. The data suggest that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
9

Year Published

1988
1988
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(38 citation statements)
references
References 21 publications
1
28
0
9
Order By: Relevance
“…[1][2][3] MVP is three-times more prevalent in patients with BJHMS than other patients and may be present in up to one third of all individuals with BJHMS. [7][8][9]29) However, there are a few reports with conflicting results on the incidence of BJHMS in MVP 15,16) and the relation between the echocardiographic features of mitral valves and elastic properties of the aortic wall and BHS in patients with both MVP and BJHMS. 7,15) In this study, we investigated the incidence of BJHMS in patients with MVP and whether BHS in MVP patients is related to the echocardiographic features of mitral valve prolapse and elastic properties of the aortic wall.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3] MVP is three-times more prevalent in patients with BJHMS than other patients and may be present in up to one third of all individuals with BJHMS. [7][8][9]29) However, there are a few reports with conflicting results on the incidence of BJHMS in MVP 15,16) and the relation between the echocardiographic features of mitral valves and elastic properties of the aortic wall and BHS in patients with both MVP and BJHMS. 7,15) In this study, we investigated the incidence of BJHMS in patients with MVP and whether BHS in MVP patients is related to the echocardiographic features of mitral valve prolapse and elastic properties of the aortic wall.…”
Section: Discussionmentioning
confidence: 99%
“…39,40) Grahame, et al reported that there was a trend towards a positive correlation between anterior mitral leaflet excursion (eg, displacement of anterior mitral leaflet) and hypermobility score but this did not reach statistical significance (r = 0.23, P > 0.05). 7) Moreover, they did not study the relationship between MLD, DMR IAOS and AOD and BHS. In the present study, BHS correlated positively with AMLT, MLD, and DMR in patients with MVP, associated with or without BJHMS in both subgroups and all study groups.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Ela pode fazer parte da normalidade como uma condição benigna em crianças 8,9 , ou estar associada a doenças hereditárias do tecido conectivo como as síndromes de Marfan e de EhlersDanlos [9][10][11] .…”
Section: Introductionunclassified